Implementing Computer-Based National Assessment in the Package C Equivalency Program: A Case Study of PKBM Tunas Mekar, Cilacap Regency - Radivan Bagas Kusuma; Joko Sutarto (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
This study aims to analyze the implementation of the Computer-Based National Assessment (Asesmen Nasional Berbasis Komputer/ANBK) in the Package C equivalency program at PKBM Tunas Mekar, Cilacap Regency, and to identify the supporting and inhibiting factors encountered by the institution. This issue emerges from limited technological infrastructure, low levels of digital literacy among learners, and regulatory demands requiring all educational providers—including non-formal education units—to administer computer-based national assessments. Employing a qualitative case study design, the research focuses on the internal dynamics of the institution in responding to educational policy mandates. The study was conducted from August to October 2025. Data were collected through interviews with four key informants (one PKBM manager, one Package C tutor, and two Package C learners), direct observations during the ANBK implementation, and a review of supporting documents. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, encompassing data reduction, data display, and conclusion verification through source and technique triangulation.The findings indicate that the implementation of ANBK at PKBM Tunas Mekar has generally aligned with national standards, as evidenced by the preparation of required facilities, dissemination of information, simulation activities, and tutor assistance. Supporting factors include government policy support, effective internal coordination, and the availability of digital literacy training. Meanwhile, the primary obstacles derive from the low digital literacy of older learners and technical disruptions related to the central examination server. This study underscores the need for policy support tailored to local institutional contexts and highlights the importance of enhancing PKBM capacity to adapt to the demands of the digital era